A review of occupational exposure to blood and blood products in medical students in a South African university - Andrew Ross; Sear Cheevers; Laura Campbell (South African Family Practice)
Background: There is a significant risk of a medical student acquiring a blood-borne pathogen following occupational exposure to blood and other bodily fluids from infected patients in the healthcare setting. Internationally and nationally, interventions have been implemented in medical schools to reduce students’ risk of acquiring a blood-borne pathogen. Few studies in South Africa have evaluated such interventions.